Endometriosis Presenting as Hydronephrosis - Ahmed Bakheet Zaharani; G.V. Soundra Pandyan (The Scientific World Journal)
The most serious urological complication of endometriosis is hydronephrotic renal atrophy secondary to ureteric involvement. As only half of these patients are symptomatic, it is commonly diagnosed late and more by the clinicians awareness and suspicion of this entity. We report a case of an unmarried young female who presented primarily with left loin pain of 2-year duration. She was found to have lower ureteric stricture by an IVU done by her referring doctor. Further workup at our center showed that she had pelvic endometriosis with hydronephrosis secondary to extrinsic ureteric endometriosis. She had a first-degree relative with the same disease. She had no menstrual problems. Diagnostic laparoscopy, biopsy of the lesion, ureteric dilatation with stenting, along with hormonal treatment was given to her as first line of treatment. There was no improvement of the ureteric obstruction even after 6 months of treatment. Finally, surgical excision of the endometrioma, left oophorectomy, along with resection of the ureteric stricture with uretero-ureterostomy was done. This case report includes details of her further management and outcome along with a brief review of literature.